Investigation Into Deformation and Failure Characteristics of the Soft-Hard Interbedded Rock Mass Under Multiaxial Compression - Li, Ang; Shao, Guojian; Li, Yaodong; Sun, Yang; Su, Jingbo; Liu, Juncheng (Frontiers in Earth Science, 2022)
In this paper, the influence of loading path, intermediate principal stress and weak layer dip angle, quantity, distribution forms and volume ratio on the deformation property, strength characteristics and failure pattern of the soft-hard interbedded rock mass are initially discussed. Firstly, the laboratory experiments of multiaxial compression failure are carried on to the soft-hard interbedded rock samples of JinPing. Three failure modes of rock samples caused by different distribution forms of weak layer under uniaxial compression and deformation property and failure characteristics of rock samples in different loading paths under biaxial compression are analyzed. And then, considering the property of strain softening, numerical models are established based on the elastic-brittle-plastic constitutive relation. The effect of weak layer dip angles, quantity, distribution forms and volume ratio on strength characteristics is further investigated. The results reveal that the failure mode of Jinping soft-hard interbedded rock samples generally follows the pattern of multi-fracture splitting under uniaxial compression and the pattern of tension-shear damage under biaxial compression; The intermediate principal stress is positively correlated with the vertical failure loading; The number of weak layer has no significant effect on the "U" type strength characteristics of samples, but as the number of weak layer increases, there is a tendency for the minimum of vertical failure loading to move forward in the direction of the smaller dip of the level.